2021
DOI: 10.3390/ijms22042101
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibits Oxidative Stress-Mediated Inflammatory Responses in Ethanol/Palmitoleic Acid-Stimulated Pancreatic Acinar AR42J Cells

Abstract: High alcohol intake results in the accumulation of non-oxidative ethanol metabolites such as fatty acid ethyl esters (FAEEs) in the pancreas. High FAEE concentrations mediate pancreatic acinar cell injury and are associated with alcoholic pancreatitis. Treatment with ethanol and the fatty acid palmitoleic acid (EtOH/POA) increased the levels of palmitoleic acid ethyl ester and induced zymogen activation and cytokine expression in pancreatic acinar cells. EtOH/POA induces nicotinamide adenine dinucleotide phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…These results indicate that Ca 2+ is upstream activator for NADPH oxidase in pancreatic acinar cells stimulated with cerulean/resistin. We previously showed that lycopene inhibits oxidative stressmediated expression of IL-6 by suppressing the NADPH oxidase activity in ethanol/palmitoleic acid-stimulated pancreatic acinar AR42J cells [52]. Our previous and present findings suggest the involvement of NADPH oxidase on the pathogenesis of acute pancreatitis.…”
Section: Mediators Of Inflammationsupporting
confidence: 70%
“…These results indicate that Ca 2+ is upstream activator for NADPH oxidase in pancreatic acinar cells stimulated with cerulean/resistin. We previously showed that lycopene inhibits oxidative stressmediated expression of IL-6 by suppressing the NADPH oxidase activity in ethanol/palmitoleic acid-stimulated pancreatic acinar AR42J cells [52]. Our previous and present findings suggest the involvement of NADPH oxidase on the pathogenesis of acute pancreatitis.…”
Section: Mediators Of Inflammationsupporting
confidence: 70%
“…Based on the previous studies [6,56] showing that HDM enter the airway epithelium and induce mitochondrial fission, it is necessary to determine whether HDM induce mitochondrial dysfunction by directly interacting with mitochondria for further study. Since HDM stimulate NADPH oxidase in airway epithelial cells [10] and lycopene inhibits NADPH oxidase in various cells [32][33][34], it should be performed to determine whether lycopene inhibits NADPH oxidase in HDM-stimulated cells. Based on the previous studies [6,56] showing that HDM enter the airway epithelium and induce mitochondrial fission, it is necessary to determine whether HDM induce mitochondrial dysfunction by directly interacting with mitochondria for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reducing ROS through lycopene may suppress TLR 4 recruitment into lipid rafts and inhibit the activation of downstream signaling pathways, such as MAPKs and NF-κB. Previously, we and others showed that lycopene inhibits NADPH oxidase activity in various cells [ 32 , 33 , 34 ]. Therefore, lycopene may inhibit NADPH oxidase in HDM-stimulated cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations